Influence of N-Arachidonoyl Dopamine and N-Docosahexaenoyl Dopamine on the Expression of Neurotrophic Factors in Neuronal Differentiated Cultures of Human Induced Pluripotent Stem Cells under Conditions of Oxidative Stress - Ekaterina Novosadova; Oleg Dolotov; Ludmila Inozemtseva; Ludmila Novosadova; Stanislav Antonov; Darya Shimchenko; Vladimir Bezuglov; Anna Vetchinova; Vyacheslav Tarantul; Igor Grivennikov; Sergey Illarioshkin (MDPI AG, 2022)
Oxidative stress (OS) is implicated in the pathogenesis of several neurodegenerative diseases. We have previously shown that N-acyl dopamines (N-ADA and N-DDA) protect the neural cells of healthy donors and patients with Parkinson's disease from OS. In this study, we assessed the effects of N-acyl dopamines on the expression of neurotrophic factors in human-induced pluripotent stem cell-derived neuronal cultures enriched with dopaminergic neurons under conditions of OS induced by hydrogen peroxide. We showed that hydrogen peroxide treatment increased BDNF but not GDNF mRNA levels, while it did not affect the secretion of corresponding proteins into the culture medium of these cells. Application of N-acyl dopamines promoted BDNF release into the culture medium. Under conditions of OS, N-DDA also increased TRKB, TRKC and RET mRNA levels. Furthermore, N-acyl dopamines prevented cell death 24 h after OS induction and promoted the expression of antioxidant enzymes GPX1, GPX7, SOD1, SOD2 and CAT, as well as reduced the BAX/BCL2 mRNA ratio. These findings indicate that stimulation of the expression of neurotrophic factors and their receptors may underlie the neuroprotective effects of N-acyl dopamines in human neurons.